Новый емкостный датчик для контроля радиальных биений валов мощных турбо- и гидрогенераторов - Левицкий, Анатолий Станиславович; Федоренко, Григорий Михайлович (НТУ "ХПИ", 2010)
The substantiation of application of capacitive sensor with rectangular form of active electrode is made. Sensor is designed for control of shaft radial runout of power turbo and hydro generators.
A new capacitive sensor for control of shaft radial runout of power turbo and hydro henerators
Keywords: машина электрическая; ротор; статор; дефект механический; электрод активный; проницаемость диэлектрическая